1971
DOI: 10.1128/jb.105.3.1224-1226.1971
|View full text |Cite
|
Sign up to set email alerts
|

Nalidixic Acid-Resistant Mutants of Escherichia coli Deficient in Isocitrate Dehydrogenase

Abstract: icd Mutants of Escherichia coli K-12, selected for their resistance to nalidixic acid, are deficient in isocitrate dehydrogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…Because the activity of these metabolic networks is relevant for the activity of the antibiotics, alterations in bacterial metabolism should influence the susceptibility to these antimicrobials. In agreement with this statement, it has been described that E. coli mutants lacking isocitrate dehydrogenase (Helling & Kukora, 1971) or aconitase B are resistant to quinolones (Gruer et al, 1997).…”
Section: Intrinsic Resistancementioning
confidence: 53%
“…Because the activity of these metabolic networks is relevant for the activity of the antibiotics, alterations in bacterial metabolism should influence the susceptibility to these antimicrobials. In agreement with this statement, it has been described that E. coli mutants lacking isocitrate dehydrogenase (Helling & Kukora, 1971) or aconitase B are resistant to quinolones (Gruer et al, 1997).…”
Section: Intrinsic Resistancementioning
confidence: 53%
“…Another mutant had an SNP mutation in the proline transport gene proV , which occurred in a multi-drug-resistant Salmonella strain (45). The third mutant had an SNP mutation in an isocitrate dehydrogenase encoding gene icd , the mutation of which has been observed in E. coli mutants resistant to nalidixic acid (46). Together, many of the identified mutated genes in the Amp-resistant strains isolated from both co-exposure and Amp-exposure conditions have resistance-related functions, which likely led to the development of Amp-resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous analysis has shown that E. coli mutants deficient in the metabolic enzyme isocitrate dehydrogenase are resistant to nalidixic acid (35). However, little work is still available in the crosstalk between metabolism (and metabolic robustness) and antibiotic resistance (57, 58), despite the fact that metabolic interventions may improve the activity of the antibiotics (33, 59-61) and that bacterial metabolism can constrain the evolution of antibiotic resistance (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that antibiotic resistance can be inter-linked to bacterial metabolism (33, 34). However, with very few exceptions (35), the mutational inactivation of genes encoding enzymes of the central carbon metabolism has not been considered to be a significant cause of antibiotic resistance in bacterial pathogens (34, 35). Our article hence shed light in the crosstalk between antibiotic resistance and central carbon metabolism in S. maltophilia .…”
Section: Introductionmentioning
confidence: 99%